Cerebrospinal fluid microRNAs as potential biomarkers in Alzheimer’s disease - Noor Eddin, Ahmed; Hamsho, Khaled; Adi, Ghaith; Al-Rimawi, Mohammed; Alfuwais, Mohammed; Abdul Rab, Saleha; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) is the leading form of dementia worldwide, but its early detection and diagnosis remain a challenge. MicroRNAs (miRNAs) are a group of small endogenous RNA molecules that regulate mRNA expression. Recent evidence suggests miRNAs play an important role in the five major hallmarks of AD pathophysiology: amyloidogenesis, tauopathy, neuroinflammation, synaptic dysfunction, and neuronal death. Compared to traditional biomarkers of AD, miRNAs display a greater degree of stability in cerebrospinal fluid. Moreover, aberrant changes in miRNA expression can be measured over time to monitor and guide patient treatment. Specific miRNA profiles and combinations may also be used to distinguish AD subjects from normal controls and other causes of dementia. Because of these properties, miRNAs are now being considered as promising and potential biomarkers of AD. This review comprehensively summarizes the diagnostic potential and regulatory roles miRNAs play in AD.